2007
DOI: 10.1353/aad.2008.0002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personal Educational Experiences and Communication Practices on the Construction of Deaf Identity in Cyprus

Abstract: The aim of the study was to investigate for the first time the impact of educational experiences on the development of Cypriot deaf people's identity. To obtain relevant information in depth, semistructured interviews were conducted with 24 Cypriot deaf individuals ages 19–54 years who had graduated from a variety of school settings. The findings indicated that the type of school, and the academic and social experiences shared within the school between the participants and their classmates and teachers, played… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…In the current study we examined the effect of genetic counseling or Connexin-26 and Connexin-30 genetic testing on deaf identify using the DIDS-R subscales to measure four orientations of deaf identity: hearing, marginal, immersion, and bicultural. Consistent with other studies [12], [51], we found that language, age, family history, education level, and high school program were significantly associated with deaf identity, and hence are important for the formation of deaf identity. However, despite adequate power, we found no evidence that genetic counseling and Connexin genetic testing, or the nature of that result (e.g., Connexin-positive, Connexin-negative) meaningfully changed participants' deaf identity, at least out to 6-months post-test result.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study we examined the effect of genetic counseling or Connexin-26 and Connexin-30 genetic testing on deaf identify using the DIDS-R subscales to measure four orientations of deaf identity: hearing, marginal, immersion, and bicultural. Consistent with other studies [12], [51], we found that language, age, family history, education level, and high school program were significantly associated with deaf identity, and hence are important for the formation of deaf identity. However, despite adequate power, we found no evidence that genetic counseling and Connexin genetic testing, or the nature of that result (e.g., Connexin-positive, Connexin-negative) meaningfully changed participants' deaf identity, at least out to 6-months post-test result.…”
Section: Discussionsupporting
confidence: 92%
“…The family is critical for the social and cognitive development of a deaf child (Danek, 1988;Greenberg & Kusche, 1989;Marschark, 1993;Warren & Hasenstab, 1986), and a highly stressed family can foster poor social competence in the deaf adolescent . Indeed, being accepted by the family is a crucial influence on the healthy development of a child's identity (Hadjikakou & Nikolaraizi, 2007). Despite the lack of literature on the experiences of deaf parents of deaf children, research suggests that they compare with those of hearing parents of hearing children (Marschark & Spencer, 2010).…”
mentioning
confidence: 99%
“…individual radio aid systems). However, D/HH children had always been signing to each other in the school yard, and some teachers had been using, in an unofficial way, total communication in their classrooms (Hadjikakou & Nikolaraizi, 2007). Nowadays, a sign language interpreter is employed at the school for the deaf.…”
Section: Mode Of Communicationmentioning
confidence: 99%